A practical perspective for chromatic orthogonality for implementing in photolithography - Godlaveeti Sreenivasa Kumar (17886683) (2023)
Theoretically, it is more challenging to anticipate the conversion and selectivity of a photochemical experiment compared to thermally generated reactivity. This is due to the interaction of light with a photoreactive substrate. Photochemical reactions do not yet receive the same level of broad analytical study. Here, we close this research gap by presenting a methodology for statistically forecasting the time-dependent progression of photoreactions using widely available LEDs. This study uses NiS/ZnO in perovskite (MAPbI3) solar cells as an additive (5 volume %). The effect of monolithic perovskite solar cells (mPSCs) on forecasting the wavelength of LEDs has been carefully investigated using various characterization methods, including X-ray diffraction (XRD) and Transmission electron microscopy (TEM). The photocatalytic activity was analyzed by measuring the voltage produced. Various factors like selectivity, stability and sensitivity were also examined. This work provides a new perspective to validate NiS/ZnO photocatalysts for predicting the wavelength of different light sources and to apply in photolithography. Other Information Published in: Scientific Reports License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1038/s41598-023-27869-w